Content Analysis on Grammar, Vocabulary and Its Context for Vocational School Textbook: Teachers’ Voices - Rebut Yuni Ernawati (Graduate Program, University of Islam Malang, 2021)
This study analyzes the tenth-grade Vocational High School English textbook, Forward an English Course for Vocational Students, from the teacher’s perspective. This is a valuable research project since its findings reveal whether the textbook can be used as a good guide for teachers to be utilized or not. The content analyzed is grammar, vocabulary, and the content related to the English used at the workplace. A survey questionnaire was used in this study to elicit the perspectives of English language teachers who are using this textbook in their classrooms along with the personal evaluation by the researcher. The findings show that the main grammatical item and vocabulary load are appropriately and sufficiently chosen for the students’ level and gradually increase in complexity to suit the growing ability of the students. The grammatical items are introduced explicitly in meaningful contexts with clear examples and explanations. The exercise of grammar helps the students to see the connection between forms and functions. The exercise of vocabulary helps the students understand their meaning and use them correctly in context. Overall, this book can be utilized properly as the teaching material for the non-native teachers to teach English in Vocational School Grade X.